Implementasi Teknologi Kontainer Docker pada Server RADIUS untuk Manajemen Autentikasi Terpusat pada Jaringan MikroTik - Andreas Damar Saputra; Febrian Wahyu Christanto (Jurnal Sistem Informasi Galuh, 2026)
The management of network infrastructure in the Semarang City Government includes 468 router sites that are managed collectively by only 7 technical personnel. The main challenge arises in meeting the Service Level Agreement (SLA) target of 99.5%, where 30 sites experienced downtime exceeding the tolerance limit of 3.72 hours due to the difficulty of local authentication coordination. This study implements a modified Network Development Life Cycle (NDLC) method, including analysis, design, laboratory simulation, and functional testing phases. As a validation phase, the system was tested in a laboratory environment integrated with 3 router sites. The test results show that the system successfully integrates FreeRADIUS, MariaDB, and daloRADIUS within a single management gateway. Based on the efficiency analysis, the RADIUS response time test yielded an average of 1142.83 ms with a difference of 211.95 ms from local authentication, thus remaining within a safe range for network operations. In addition, a satisfaction survey of technical personnel showed positive results with 75% expressing satisfaction and 25% quite satisfied. In conclusion, this Dockerized RADIUS model is worthy of recommendation as a standardization solution to accelerate troubleshooting and maintain public service availability.